Biomimetic mechanical properties and its role in restorative dentistry - Basudan, Thuraya Abdulrahim; Alqahtani, Wafa Mansour; Almughalliq, Fatimah Abdullah; Alshahrani, Atyaf Saeed; Aldawsari, Atheer Mubarak; Algouzi, Atheer Ali; Hamdoon, Anas Riyadh; Alkarim, Abdulaziz Saleh; Shalwan, Amal Abdulrahman Al; Alhuzili, Ghadah Hamid; Maghrabi, Nusaybah Hamzah (International Journal Of Community Medicine And Public Health, 2021)
The main aim of introducing biomimetic materials is to achieve successful remineralization using biocompatible and optimally functioning materials that can be used to manage diseased and defective tissues in a minimally invasive process. Recently, evidence shows that many biomimetics was introduced with excellent advantages and favorable outcomes in the different fields of dentistry. A wide acceptance of biomimetics was reported in the field of dentistry as the modalities were efficaciously applied in the different endodontic and restorative procedures. In the present literature review, we have discussed the biomimetic mechanical characteristics of the different restoration materials that are currently used in the field of restorative dentistry. The current evidence supports the use and applications for biomimetics in the field of restorative dentistry based on the extensively reported evidence regarding the mechanical and functional characteristics of these modalities which mimic the functions of normal teeth. Accordingly, these modalities can be used to solve the underlying clinical challenges that are routinely faced in the settings of restoration. Furthermore, different materials were introduced and evaluated for their efficacies, and the clinical decision of these materials is based on many factors and should be taken based on dentist-and-patient interaction.